Nano-hydroxyapatite Pickering emulsions as edible mayonnaise-like food sauce templates: A novel approach for food design - Relvas, Maria Eduarda (2024)
Pickering emulsions have the potential to enhance product stability and provide opportunities to create functional solutions that align with labelling requirements. The present work aims to develop Pickering emulsions stabilised by nano-hydroxyapatite (n-HAp) particles to replace traditional mayonnaises. The study addresses the effect of n-HAp solid particle concentration (5–15 wt%) and oil-water ratio (50:50, 60:40, 70:30, and 80:20, v/v) on emulsion stability, rheological properties, and oxidative stability. The results indicate that the produced Pickering emulsions have good stability for the tested period of 90 days, except for the 80:20 o/w emulsion that undergone a prompt quick phase separation. The Pickering emulsions produced with higher n-HAp concentration or oil content have a semi-solid structure, rendering them desirable options for replicating the texture of traditional mayonnaises. Regarding oxidative stability, the Pickering emulsions showed considerably improved stability compared to commercial mayonnaises (∼13 times higher), suggesting higher resistance to peroxidation and a longer shelf-life.